Pemberdayaan Kader PKK Dalam Pencegahan Stunting di Kelurahan Gedong Jakarta Timur - Mochammad Ryan Amarullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Program implementation is a series of activities carried out by individuals or groups in the form of implementing activities supported by policies, procedures, and resources intended to bring results to achieve predetermined goals and objectives. This study aims to determine and explain the implementation of the stunting program through the Empowerment of Family Welfare (PKK) in Stunting Prevention and explain the obstacles to the implementation of the program through the Empowerment of Family Welfare (PKK) in Stunting Prevention in Gedong Village. This research uses descriptive qualitative methods, data collection by means of interviews, observation and documentation and the determination of informants using non-probability. The parties used as research subjects are administrators and members of the Family Empowerment and Welfare (PKK) in Gedong village and the object of research is the implementation of the stunting program for toddlers and mothers. The results of this study are evidenced by the existence of children with stunting getting better after the implementation of programs from the government, such as food intake with balanced nutrition monitoring height and weight in these toddlers every month. PKK cadres in Gedong Village in implementing programs to improve social welfare need to be carried out because the stages of implementing the stunting program have a positive impact on the beneficiaries of social services.